Academic Orientation in Preschool Education - Samsudin, Mohamad; Rahim, Husni; Saepudin, Didin (International Journal for Educational and Vocational Studies, 2021)
Currently, preschool education has evolved, even it has been revolutionized. This fact is shown by the large content of academic teaching materials such as reading, writing, and arithmetic which is still controversial must be taught in preschool education, which seems to be a compulsory subject for preschool children. Although government regulations have regulated properly and ideally how preschool education should be implemented, ironically due to competition between preschool institutions and the demands of parents, many preschool institutions fulfill their curricula with academic content. This study aims to obtain an overview of the academic-oriented preschool learning process in planning, implementation, and evaluation.